Structural break in the Norwegian LFS due to the 2021 redesign - Hungnes, Håvard,Skjerpen, Terje,Hamre, Jørn Ivar,Jansen, Xiaoming Chen,Dinh Quang Pham,Sandvik, Ole (Statistics Norway, Research Department, 2022)
The labour force surveys (LFSs) on all Eurostat countries underwent a substantial redesign in January 2021. To ensure coherent labour market time series for the main indicators in the Norwegian LFS, we model the impact of the redesign. We use a state-space model that takes explicit account of the rotating pattern of the LFS. We also include auxiliary variables related to employment and unemployment that are highly correlated with the LFS variables we consider. The results of a parallel run are also included in the model. This paper makes two contributions to the literature on the effects of LFS redesign. First, we suggest a symmetric specification of the process of the wave-specific effects. Second, we account for substantial fluctuations in the labour force estimates during the Covid-19 pandemic by applying time-varying hyperparameters. Likelihood-ratio tests and examination of the auxiliary residuals show the latter to be warranted.
10419/268063
Keywords: Graue Literatur; State-space models; Auxiliary information; Labour market domains; Level shifts; Covid19; Norway